Central Bank Digital Currencies: Benefits, Risks and the Role of Blockchain Technology - Jonas Groß; Manuel Klein; Philipp Sandner (Wirtschaftsdienst)
Abstract Blockchain technology can be the basis for future currencies. Numerous central banks are experimenting with this distributed ledger technology to map currencies on a blockchain basis in the future (central bank digital currencies, CBDCs). In this article, we explore motives for the introduction of CBDCs. The main motives are higher financial stability, higher security and efficiency of payment systems and a higher degree of automation of business processes. Furthermore, the risks of CBDCs are presented and the current state of development at the European Central Bank (ECB) is discussed.